MEMBACA GERAKAN ISLAM RADIKAL DAN DERADIKALISASI GERAKAN ISLAM - Muzayyin Ahyar (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2015)
This study focussed on many radical Islamic movements in Solo as the objects of research, especially the Islamic movements oftenly called as Tim Hisbah. Applying the approach of political sociology, this research will capture that phenomenons of religious radicalism are not merely problem of religious ideology, but also socio-political problem. Frammed by the social theories such as the theory of identity and social movements, included political opportunity structure, framing process, and the mobilizing structure this study showed that radicalism is an effort to establish identity by utilizing mass network (Muslim), mobilization, framing process, and advantaging political opportunities (democratic nature). In addition to relate to religious de-radicalization in Indonesia, this research argued that Islamic radicalism is not only a religious phenomenon that must be solved solely by de-radicalization of Islamic thought and ideology, but also a phenomenon that can be discussed by other sciences such as social, political and economic sciences.